Facial talon cusp: A rarity, report of a case with one year follow up and flashback on reported cases - Vinaya Kumar Kulkarni; Pinky Choudhary; Arpana V Bansal; Jeevanand Deshmukh; Mahesh Kumar Duddu; N D Shashikiran (Wolters Kluwer Medknow Publications, 2012)
Talon cusp is a relatively uncommon developmental anomaly characterized by cusp-like projections, usually presenting on palatal/lingual surface of the anterior teeth. This cusp resembles an eagle's talon, and hence the name. Normal enamel and dentin covers the cusp, which may or may not contain an extension of pulp. Presence of this anomalous cusp on the facial surface of an anterior tooth is a rare finding and very few cases have been reported in the literature. In most instances, such cusps are associated with clinical problems such as poor esthetics and caries susceptibility. Management of such cases requires a comprehensive knowledge of the clinical entity as well as the problems associated with it. This case report presents a facial talon cusp on the maxillary left central incisor of a 10 year old boy, which was conservatively treated. Vitality of the affected tooth was maintained and followed up for a period of 1 year.